Apes in the Anthropocene: flexibility and survival. (April 2015) - Hockings, Kimberley J.; McLennan, Matthew R.; Carvalho, Susana; Ancrenaz, Marc; Bobe, René; Byrne, Richard W.; Dunbar, Robin I.M.; Matsuzawa, Tetsuro; McGrew, William C.; Williamson, Elizabeth A.; Wilson, Michael L.; Wood, Bernard; et al.
Highlights Few great ape habitats are entirely unaffected by human activities. Anthropogenic impacts are triggering behavioural flexibility in great apes. Research across the 'anthropogenic continuum' can advance pure and applied science. Survival of many ape populations requires finding ways for human–ape coexistence.